2004
DOI: 10.1071/ah040330
|View full text |Cite
|
Sign up to set email alerts
|

Impact on public hospitals if private health insurance rates in Victoria declined

Abstract: The additional cost of treating acute care type Victorian private patients as public patients in Victorian public hospitals based on the current public sector payment model and rates was calculated, as was the loss of health fund income to public hospitals. If all private cases became public the net recurrent cost would be $1.05 billion assuming all patients were still treated. If private health insurance (PHI) uptake had declined to 23.3% as was projected without Lifetime Health Cover and the 30% rebate, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…10 This increased premiums for those initially taking up private hospital insurance after the age of 30 by 2% for each year over 30, up to a maximum of 70%. 12,13 These three measures brought about an increase in insurance levels from around 32% at the start of 2000 to a high of around 45% at the end of 2000, although levels have since dropped slightly 7 (Box 1).…”
Section: What Are the Implications For Practitioners?mentioning
confidence: 99%
“…10 This increased premiums for those initially taking up private hospital insurance after the age of 30 by 2% for each year over 30, up to a maximum of 70%. 12,13 These three measures brought about an increase in insurance levels from around 32% at the start of 2000 to a high of around 45% at the end of 2000, although levels have since dropped slightly 7 (Box 1).…”
Section: What Are the Implications For Practitioners?mentioning
confidence: 99%
“…There is a growing body of literature examining the effects of these reforms [6–14]. It is generally accepted that Life Time Health Cover was the major policy increasing insurance coverage in the Australia population [9,10].…”
Section: Policy Reformsmentioning
confidence: 99%
“…Research has also shown that middle and higher income earners were more likely to take up the 30% rebate in PHIAA than lower income earners [7]. Vigorous debate also continues on the influence of private health insurance on the public health‐care system, particularly on waiting times and public hospital demand more generally [11–14].…”
Section: Policy Reformsmentioning
confidence: 99%